UMPSA, UTHM and UiTM students participate in Malaysia China Advanced TVET International Mobility programme MyChaT 2024 to explore automotive field - Mimi Rabita, Abd Wahit (UMPSA, 2024)
KUALA LUMPUR, 25 May 2024 - A total of 21 students and five staff of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) participated in the Malaysia-China Advanced TVET International Mobility Programme (MyChaT 2024) from 25 May to 5 June 2024.